The Role of Awareness and Cognitive Aptitudes in L2 Predictive Language Processing. (26th September 2018) - Curcic, Maja; Andringa, Sible; Kuiken, Folkert
Abstract: This study investigated whether second language (L2) learners can develop predictive processing of determiners after a brief exposure to a novel language, and whether this depends on learners' awareness for the target structure and their cognitive aptitudes. One hundred L2 learners received auditory exposure to a miniature language based on Fijian that included a determiner–noun agreement pattern. Learners' processing of determiners was measured using a picture‐matching task with eye tracking. We found that learners learned to anticipate the coming noun based on the determiner; they also gained a speed advantage. Learners' awareness played a crucial role in such anticipatory processing; only learners who were aware that determiners helped them during the test (i.e., prediction‐aware learners) showed signs of anticipatory processing. The aptitude variables did not modulate learners' processing abilities, but there were links between aptitude and learners' abilities to develop different levels of awareness.